2017
DOI: 10.1089/zeb.2016.1383
|View full text |Cite
|
Sign up to set email alerts
|

The Karyotype of Microsternarchus aff. bilineatus: A First Case of Y Chromosome Degeneration in Gymnotiformes

Abstract: Various species and lineages that until recently were identified as Microsternarchus bilineatus (Hypopomidae, Gymnotiformes) have a widespread distribution in the Amazon and Orinoco River basins and across the Guiana shield. Recent molecular studies show five distinct lineages for Microsternarchus from different localities. These results suggest that this previously monotypic genus actually consists of more than one species. Here, we describe the karyotype of M. aff. bilineatus from the Cururutuia River (Braga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Cytogenetics has been an important tool in cytotaxonomy and has proved to be very useful in understanding the evolutionary processes behind the diversification of Gymnotus . The Gymnotiformes order has considerable variation, not only in diploid number (from 2 n = 24 in Apteronotus albifrons , Howell, 1972 ; Almeida-Toledo et al, 1981 ; Mendes et al, 2012 ; to 2 n = 74 in Rhabdolichops cf eastward , Suárez et al, 2017 ) but also in the karyotype formula and location of repetitive sequences (Fernandes et al, 2005 ; Almeida-Toledo et al, 2007 ; Silva et al, 2009 ; da Silva et al, 2013 ; Jesus et al, 2016 ; Araya-Jaime et al, 2017 ; Batista et al, 2017 ; Sousa et al, 2017 ; Takagui et al, 2017 ). Recently, fluorescence in situ hybridization (FISH), has played an important role in understanding the genome structure of fish species (Yi et al, 2003 ; Cabral-de-Mello and Martins, 2010 ; Martins et al, 2011 ; Vicari et al, 2011 ; Gornung, 2013 ; Knytl et al, 2013 ; Yano et al, 2017 ) and molecular cytogenetic studies in Gymnotiformes have shown dynamic reorganization, including pericentric inversions observed through repetitive DNA position (Fernandes et al, 2017 ), sequence dispersion via transposable elements and the association between different repetitive sequences (Utsunomia et al, 2014 ; da Silva et al, 2016 ; Machado et al, 2017 ) and the presence of different sex chromosome systems (Margarido et al, 2007 ; Henning et al, 2008 , 2011 ; da Silva et al, 2011 , 2014 ; Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetics has been an important tool in cytotaxonomy and has proved to be very useful in understanding the evolutionary processes behind the diversification of Gymnotus . The Gymnotiformes order has considerable variation, not only in diploid number (from 2 n = 24 in Apteronotus albifrons , Howell, 1972 ; Almeida-Toledo et al, 1981 ; Mendes et al, 2012 ; to 2 n = 74 in Rhabdolichops cf eastward , Suárez et al, 2017 ) but also in the karyotype formula and location of repetitive sequences (Fernandes et al, 2005 ; Almeida-Toledo et al, 2007 ; Silva et al, 2009 ; da Silva et al, 2013 ; Jesus et al, 2016 ; Araya-Jaime et al, 2017 ; Batista et al, 2017 ; Sousa et al, 2017 ; Takagui et al, 2017 ). Recently, fluorescence in situ hybridization (FISH), has played an important role in understanding the genome structure of fish species (Yi et al, 2003 ; Cabral-de-Mello and Martins, 2010 ; Martins et al, 2011 ; Vicari et al, 2011 ; Gornung, 2013 ; Knytl et al, 2013 ; Yano et al, 2017 ) and molecular cytogenetic studies in Gymnotiformes have shown dynamic reorganization, including pericentric inversions observed through repetitive DNA position (Fernandes et al, 2017 ), sequence dispersion via transposable elements and the association between different repetitive sequences (Utsunomia et al, 2014 ; da Silva et al, 2016 ; Machado et al, 2017 ) and the presence of different sex chromosome systems (Margarido et al, 2007 ; Henning et al, 2008 , 2011 ; da Silva et al, 2011 , 2014 ; Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome fusions were identified herein as important events in the diversification of Brachyhypopomus , and have also been observed in Microsternarchus bilineatus ( de Jesus et al, 2016 ; Batista et al, 2017 ). In contrast, fusions have not been registered among species of Rhamphichthyidae (the sister group to Hypopomidae), which exhibits a karyotype evolution characterized by 2 n conservation (50 chromosomes) and chromosome inversions ( Cardoso et al, 2011 ; Mendes et al, 2012 ; Silva et al, 2013 ).…”
Section: Discussionmentioning
confidence: 61%
“…Compared to other rhamphichthyids that have 2n = 50, the karyotype of G. britskii suggested a reduction in the 2n, indicating that chromosome rearrangements, such as centric fusions that can alter the chromosome number may have occurred during the diversification of this group. Chromosome fusions were identified as important events in the diversification of Hypopomidae (the sister group of Rhamphichthyidae), in which the diploid number varies between 36 chromosomes, as in B. brevirostris, and 48 chromosomes, as in M. bilineatus (de Jesus et al, 2016;Batista et al, 2017;Cardoso et al, 2018). In Rhamphichthyidae, the chromosomic data of G. britskii alter the paradigm of karyotype evolution characterized by 2n conservation (50 chromosomes) and chromosome inversions (Cardoso et al, 2011;Mendes et al, 2012;Silva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among the other Rhamphichthyidae, cytogenetic information is available only for Hypopygus lepturus Hoedeman, 1962(Almeida-Toledo, 1978, Steatogenys duidae (La Monte, 1929), S. elegans (Steindachner, 1880) (Cardoso et al, 2011), Rhamphichthys hahni (Meinken, 1937), R. pantherinus Castelnau, 1855 (cited as R. marmoratus) and R. rostratus (Linnaeus, 1766) (Mendes et al, 2012;Silva et al, 2013). Among the Hypopomidae, it is available for Hypopomus artedi (Kaup, 1856) (Almeida-Toledo, 1978, eight Brychyhypopomus species (Almeida-Toledo, 1978;Mendes et al, 2012;Cardoso et al, 2018) and Microsternarchus bilineatus Fernández-Yépez, 1968(de Jesus et al, 2016Batista et al, 2017).…”
Section: First Chromosomal Analysis Of Gymnorhamphichthys Britskiimentioning
confidence: 99%
See 1 more Smart Citation